MULTIWAVELENGTH SOURCE USING A BRILLOUIN FIBER LASER - HARUN, S. W.; SHIRAZI, M. R.; ABDUL-RASHID, H. A.; AHMAD, H. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
A multiwavelength laser operating on the basis of stimulated Brillouin scattering (SBS) is demonstrated in a single mode fiber (SMF) coupled with a feedback loop and an optical circulator. Ten simultaneous Stokes and anti-Stokes lines are obtained with a line spacing of either 0.08 or 0.16 nm at a Brillouin pump (BP) power of 14 dBm. The use of a 50/50 fused coupler gives the highest number of lines at a Stokes power of approximately 8 dBm. The anti-Stokes lines are generated by four-wave mixing and bidirectional operation of the system. This Brillouin fiber laser (BFL) is capable of operating at any wavelength, depending completely on the BP wavelength. Due to the built-in feedback mechanism, its operation is free from the need for any additional active linear gain medium, such as erbium-doped fibers used in a Brillouin erbium fiber laser. Further, the SMF can in principle be replaced with a highly nonlinear waveguide, such as a photonic crystal waveguide, to make a compact multiwavelength BFL.